2013
DOI: 10.5897/jmld2013.0072
|View full text |Cite
|
Sign up to set email alerts
|

Endemicity of schistosomiasis in some parts of Anambra State, Nigeria

Abstract: Investigation on the prevalence of infections with schistosoma was carried out amongst inhabitants of two local government areas (LGAs), Nigeria between October 2007 and September 2008. A total of 2064 randomly selected subjects had their urine and stool samples examined for eggs of Schistosoma and 323 (15.7%) were excreting eggs of S. haematobium in their urine with geometric mean egg count (GMEC) of 10.1 eggs/10 ml of urine. No eggs of S. mansoni were found. Prevalence of infection varied between 12.8 and 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
2
12
1
Order By: Relevance
“…Hence, provision for their treatment should be considered in control programs. In accordance with our findings, previous studies have shown the age-dependent occurrence of schistosomiasis and indicated that the prevalence peak occurs during the adolescence and then decreases slowly 26 , 30 , 46 , 47 . The excessive mobility of adolescents in terms of swimming, bathing and playing in open water could explain the higher prevalence rate in this age group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hence, provision for their treatment should be considered in control programs. In accordance with our findings, previous studies have shown the age-dependent occurrence of schistosomiasis and indicated that the prevalence peak occurs during the adolescence and then decreases slowly 26 , 30 , 46 , 47 . The excessive mobility of adolescents in terms of swimming, bathing and playing in open water could explain the higher prevalence rate in this age group.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, another study from Ogun State reported that the prevalence of S. mansoni and S. haematobium infections was 2.3% and 0.6% respectively 29 . A recent study among 2,064 participants from Anambra State, Nigeria reported that 15.7% of them were infected with S. haematobium while none of the participants was found to be positive for S. mansoni 30 . Moreover, it was shown that schistosomiasis is focally distributed and prevalence rates vary in different communities and locations of Nigeria 28 , 31 , 32 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The mean intensity of infection was 30.27(17.97-42.57) eggs/10 ml of urine in this study. Previous records from Anambra State, South East Nigeria (10.1 eggs/ 10 ml of urine), Kaduna State, North West Nigeria (73.93 eggs/10 ml of urine) and the Republic of Chad (<13.5 eggs/10 ml of urine) further confirm the focal nature of urogenital schistosomiasis [ 20 – 22 ]. These differences might be as a result of seasonal variations, proximity of infested water bodies, natural tendency of subjects towards recreation (swimming and playing in shallow water), and the state of social amenities in both the study area and some states in Nigeria mentioned above.…”
Section: Discussionmentioning
confidence: 69%
“…It is speculated that their exposure to river water may not only be because of ignorance but also poverty, as the source of water "before civilization of getting bore hole, was majorly from the river." Ugochukwu et al (2013) noted that rivers and ponds, with divers' freshwater environment, offer favourable habitats for aquatic snails that serve as an intermediate host for schistosomiasis. As such, living in this environment without other sources of water supply can lead to a high prevalence of schistosomiasis disease.…”
Section: Discussion Of Findingsmentioning
confidence: 99%